Vitamin D Genomics: From In Vitro to In Vivo - Carlberg, Carsten (Frontiers in Endocrinology, 2018)
The vitamin D3 metabolite α,25-dihydroxyvitamin D3 (1,25(OH)2D3) is the exclusive high-affinity ligand of the vitamin D receptor (VDR), a transcription factor with direct effects on gene expression. Transcriptome- and epigenome-wide data obtained in THP-1 human monocytes are the basis of the chromatin model of vitamin D signaling. The model describes, how VDR’s spatio-temporal binding profile provides key insight into the pleiotropic action of vitamin D. The transcription of some 300 primary target genes is significantly modulated through the action of genomic VDR binding sites in concert with the pioneer transcription factor PU.1 and the chromatin organizer CTCF. In parallel, the short-term vitamin D intervention study VitDbol (NCT02063334) was designed, in order to extrapolate insight into vitamin D signaling from in vitro to in vivo. Before and 24 h after a vitamin D3 bolus chromatin and RNA were prepared from peripheral blood mononuclear cells for epigenome- and transcriptome-wide analysis. The study subjects showed a personalized response to vitamin D and could be distinguished into high, mid and low responders. Comparable principles of vitamin D signaling were identified in vivo and in vitro concerning target gene responses as well as changes in chromatin accessibility. In conclusion, short-term vitamin D supplementation studies represent a new type of safe in vivo investigations demonstrating that vitamin D and its metabolites have direct effects on the human epigenome and modulate the response of the transcriptome in a personalized fashion.